Dynamics of inflation determinants under dual monetary system: empirical evidence from Malaysia - Wiranata Kusuma, Dimas Bagus; Kassim, Salina; Fikri, Muhammad (2011)
Ensuring low and stable price environment has been one of the major macroeconomic objectives in most economy throughout the globe. Indeed, a stable price environment is an indication of a healthy economy as it provides an optimum environment for creation of real economic activity. In a stable price environment, economic agents are able to plan ahead in major economic decisions, let it be in investment, consumption, or production activities. Thus, understanding factors determining inflation is highly relevant and is the hallmark for effective macroeconomic stabilization policies. This study attempts to address two research questions: (1) what are the causes of inflation in a conventional monetary system compared to an Islamic monetary system? (2) Would inflation situation be different in a conventional monetary system compared to an Islamic monetary system? In efforts to achieve its objectives, the study analyzes the behavior of inflation in the two different monetary systems. First, under the conventional monetary system, the study empirically analyzes the inflation dynamics with several possible determinants of inflation, namely excess money supply from money creation or fiat money, excess money supply from credit creation or fractional reserve banking, interest rate, and exchange rate. Second, under the Islamic monetary system, the following variables are considered in the analysis: Islamic money, PLS return, and gold price. As for the dependent variable, several measures of inflation are used to ensure consistency of the findings such as CPI inflation, food inflation, administered inflation, and expected inflation. The study analyzes monthly data covering the period from January 1995 to February 2011. For comparative purposes and more enriching discussions, the period of analysis is being divided into various sub-periods, namely: (1) pre-crisis period - January 1995-December 1996; (2) during crisis period I - January 1997-December 1998; (3) post-crisis period - January 1999-December 2006, and (4) during crisis period II – January 2007-February 2011. In the methodology, the study relies on the Vector Auto Regression. Additionally, to determine the inter-relationship among the variables, innovation accounting of variance decomposition analysis is also adopted. The study finds that when the main three conventional sources of inflation of fiat money, interest rate and exchange rate are replaced by their Islamic counterparts variables of Islamic money, PLS return, and gold price, the rate of inflation drops significantly. In addition, the study provides empirical evidence that the conventional variables of fiat money, interest rate and exchange rate contribute significantly in explaining the variations of inflation in Malaysia. Based on the findings, the study concludes that increasing the share of PLS-based Islamic finance and relying on gold in the payment system would contribute towards greater price stability in the economy. Thus, there is a need to reduce the dependency on the riba-based system as the study has empirically shown that the riba-based system is inflation generating and would lead to macroeconomic instability